Legal Certainty in Performance-Based Civil Servant Promotions: The Role of Individual Performance Targets - Syafriadi Lubis; Rahmat Ramadhani (Abdurrauf Social Science, 2026)
Civil servant (PNS) performance assessment constitutes a fundamental basis for career advancement, particularly in promotion processes, and therefore must ensure legal certainty and objectivity. From a state administrative law perspective, performance assessment represents an administrative act with direct legal consequences for the status and rights of civil servants. This study aims to analyze the legal framework governing civil servant promotions and to examine the role of Individual Performance Targets (SKP) as a parameter of legal certainty. This research employs a normative legal method using statutory and conceptual approaches to assess relevant legal norms and doctrines. The findings indicate that promotion decisions qualify as administrative decisions whose validity depends on objective, measurable, and procedurally compliant performance assessments. However, in practice, SKP is frequently treated as a formal administrative requirement and does not adequately reflect substantive performance. The novelty of this study lies in positioning SKP as a legal parameter in determining the validity of promotion decisions. The study recommends strengthening the substantive implementation and monitoring of SKP to ensure legal certainty and protection of civil servant rights.